2010
DOI: 10.1002/hed.21127
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyosarcoma of the larynx as a local relapse of squamous cell carcinoma—Report of an unusual case

Abstract: Leiomyosarcoma after SCC is very uncommon. A connection between both seems likely in this case. Transdifferentiation, also seen in other tumors or carcinosarcomas, could be based on aberrant differentiation of a pluripotent stem cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…[3] Radiation induced sarcomas or sarcomatoid dedifferentiation of squamous cell carcinomas after irradiation has been proposed; however radiotherapy has not been found to be present in the history of most patients with LLMS. [4] An interesting case of LLMS that occurred after primary laryngeal squamous cell carcinoma reported by Völker et al [4] had also not received radiotherapy after surgical treatment of his primary disease. Kara et al [5] reported two cases of LLMS with rare association of squamous cell carcinoma of the larynx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Radiation induced sarcomas or sarcomatoid dedifferentiation of squamous cell carcinomas after irradiation has been proposed; however radiotherapy has not been found to be present in the history of most patients with LLMS. [4] An interesting case of LLMS that occurred after primary laryngeal squamous cell carcinoma reported by Völker et al [4] had also not received radiotherapy after surgical treatment of his primary disease. Kara et al [5] reported two cases of LLMS with rare association of squamous cell carcinoma of the larynx.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][11][12][13][14][15] In general, partial laryngectomy is recommended for patients with early stage tumors and postoperative radiotherapy might have a role in allowing a more limited surgical resection or it might be a complementary therapy to improve loco-regional control. [4][5][6][7][8][11][12][13][14][15] Neck dissection is indicated for clinically positive cervical nodal disease. [14] Elective neck dissection is not indicated unless there are clinically positive nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the same p53 mutations are present in both parts of these biphasic tumours 12 , 13 . Völker et al investigated the losses and gains on some chromosomes in a metachronous tumour of the larynx, and suggested that these changes might be related to transdifferentiation of the tumour from squamous cell carcinoma to leiomyosarcoma 14 …”
Section: Discussionmentioning
confidence: 99%
“…It was first reported by Jackson and Jackson in 1939 2 . To the best of our knowledge, 62 cases of LLMS have been reported in the English‐language literature 1,3–55 …”
Section: Introductionmentioning
confidence: 99%